FOREWORD - Subiotto, Namita (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
In the 7th issue of “Palimpsest” there are 25 papers (twelve original scientific papers, ten theoretical papers, one review paper and two book reviews) by authors from eleven countries: Macedonia, Turkey, France, Burundi, Benin, Switzerland, Serbia, Ivory Coast, Senegal, Morocco, and Algeria, written in Macedonian, English, French and Turkish. The papers cover all the sections of the journal. The biggest number of papers belong to the Literature section (a total of twelve papers in which classical and contemporary Macedonian, Russian, Turkish, Spanish, French, and Algerian authors as well as folk arts are the subject of research), followed by seven papers in the “Language” section (with research conducted in the following languages: Macedonian, Turkish, French, Nepalese, Kirundi), two papers are dedicated to the cultural research (on the ethnocoreological characteristics of the folk dances “Teshkoto” and “Lesnoto” and the influence of furniture on the cultural aspect of housing space in the first half of the 20th century in Skopje), two papers are in the field of English language teaching methodology, and finally the journal concludes with a review of the doctoral dissertation on language errors related to inflected words in the Macedonian language among elementary school students by Maria Grkova as well as a review of the literary monograph written by Venko Andonovski on the literary texts as a process.